Strategic Spatial Planning in Lebanon: An International “Recipe”. The Case of The Union of Municipalities - Darwich, Rozana (European Spatial Research and Policy, 2018)
In 1977 the municipal law authorised the creation of unions of municipalities in Lebanon. However, only recently have they actually begun to emerge; 13 unions existed in 1990 while 57 were created by 2017. Over the last decade these unions have assumed an important role within the local dynamics, particularly in the field of strategic planning. This article aims to analyse that shift by answering the following questions: first, what is the positioning of the unions, as institutional planning actors, on the planning chessboard? Second, how was strategic planning transferred to the unions of municipalities? And finally, what was the echo of this transfer on other national or local actors?